The Informational Value of Job Search Data and the Dynamics of Search Behaviour: Evidence from Hungary - John Micklewright; Gyula Nagy (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 1999)
Labour market analysis places much emphasis on the concept of search. But there is insufficient empirical information on (a) the relationship between reported search and job-finding and (b) how search behaviour changes over a spell without work. We investigate these issues using a sample constructed from Hungarian labour force survey panel data of the flow from jobs to the state of "joblessness". The results on job exits call into question aspects of the standard international classification of "unemployment" and "out of the labour force". Transitions during joblessness in and out of search and the various categories of non-search are found to be only modest.
Keywords: 330